Degradation process of lead chromate in paintings by Vincent van Gogh studied by means of synchrotron X-ray spectromicroscopy and related methods. 1. Artificially aged model samples - Monico, Letizia; Van der Snickt, Geert; Janssens, Koen; De Nolf, Wout; Miliani, Costanza; Verbeeck, Johan; Tian, He; Tan, Haiyan; Dik, Joris; Radepont, Marie; Cotte, Marine (Analytical chemistry (Washington), 2011)
On several paintings by artists of the end of the 19th century and the beginning of the 20th Century a darkening of the original yellow areas, painted with the chrome yellow pigment (PbCrO(4), PbCrO(4)·xPbSO(4), or PbCrO(4)·xPbO) is observed. The most famous of these are the various Sunflowers paintings Vincent van Gogh made during his career. In the first part of this work, we attempt to elucidate the degradation process of chrome yellow by studying artificially aged model samples. In view of the very thin (1-3 μm) alteration layers that are formed, high lateral resolution spectroscopic methods such as microscopic X-ray absorption near edge (μ-XANES), X-ray fluorescence spectrometry (μ-XRF), and electron energy loss spectrometry (EELS) were employed. Some of these use synchrotron radiation (SR). Additionally, microscopic SR X-ray diffraction (SR μ-XRD), μ-Raman, and mid-FTIR spectroscopy were employed to completely characterize the samples. The formation of Cr(III) compounds at the surface of the chrome yellow paint layers is particularly observed in one aged model sample taken from a historic paint tube (ca. 1914). About two-thirds of the chromium that is present at the surface has reduced from the hexavalent to the trivalent state. The EELS and μ-XANES spectra are consistent with the presence of Cr(2)O(3)·2H(2)O (viridian). Moreover, as demonstrated by μ-XANES, the presence of another Cr(III) compound, such as either Cr(2)(SO(4))(3)·H(2)O or (CH(3)CO(2))(7)Cr(3)(OH)(2) [chromium(III) acetate hydroxide], is likely.